Râja Malla dan Rajamala dalam Wirataparwa - YB. Rahno Triyogo (Institut Seni Indonesia Surakarta, 2020)
Râja malla and Rajamala in the Wirataparwa describe the occurrence of text variations in the Old Javanese Wirataparwa into the New Javanese Virataparwa. The events of this text variation are described based on the reception theory. The results show that the reception can be found, first, in the shift of pronunciation from the Old Javanese tradition to the New Javanese tradition. Second, the shift in meaning which originally meant the king of fighting turned into the king of ‘disease’. Third, at first it was only a title which meant fighting king, then in the New Javanese tradition it emerged as a self-name, namely Rajamala, a Wirata officer. Fourth, what was originally in the form of prose was later changed into the form of macapat songs, and in the form of performing arts with various titles.